Efektifitas Pola Tata Ruang Terhadap Sistim Sirkulasi Mesjid Al-Mukarramah –Pekanbaru - Wati Masrul; Boby Samra (Asosiasi Dosen Akuntansi Indonesia, 2021)
The mosque is a physical facility for Muslims to perform the fardhu prayer. Therefore, in the construction of mosques, it should be made as effective as possible in order to maintain the rules that have been set in maximizing Muslim worship activities. Through community service activities, the team tried to examine the spatial pattern of the mosque against the main rooms needed to support the creation of comfort in the implementation of Muslim worship at the Al-mukarramah mosque in Pekanbaru. The main room in question is a prayer room, ablution facilities and toilets. By examining the effectiveness of the room arrangement of the Al-Mukarramah mosque, it will basically affect the circulation patterns that will be formed in the mosque so that it is hoped that it can better maintain the rules or regulations that have been set in the implementation of the fardhu prayer. This service is carried out in several stages including data collection, analysis, and drafting of concepts and circulation arrangement designs that are suitable for mosques so that the effectiveness of spatial planning and circulation in the Masjid Al-Mukarramah Pekanbaru is created.